Polymer Composites and Polymer Testing : selected, peer reviewed papers from the 2012 International Symposium on Polymer Composites and Polymer Testing (ISPCPT 2012), March 23-25, 2012, Hangzhou, Zhejiang, China - Mao, Hongkui (Advanced materials research ;, 2012)
These are the proceedings of the International Symposium on Polymer Composites and Polymer Testing (ISPCPT 2012), held on the 23rd to 25th March, 2012, in Hangzhou, Zhejiang, China. They cover topics related to Polymer Composites and Applied Materials, Applied Mechanics and Manufacturing.